(untitled) (Historia, 2021)
The 20th to 21st century has seen dramatic changes in the amount of available information from which researchers can obtain insights into people’s past experiences. Traditionally, historical insights were derived mainly from archival and physical sources. Oral interviews also offered new perspectives as well as challenges for the interpretation of histories. Increasingly, social media provide researchers not only audio and/or visual material, but also unique combinations of these two mediums. The wave of technological innovation affords the ordinary person the opportunity to record, store and share his or her life experiences. The extent to which this is occurring is also testimony of the information age. For historians this not only provides a rich array of sources, but also requires them to take new responsibility regarding internal and external source criticism, along with a keen sense of knowledge of the available technologies. As one such platform YouTube is being used increasingly to capture and share life experiences. One such example the 2015-2017 drought in the Vaal Triangle. For contemporary historians, social media provides unique opportunities to investigate, with the appropriate analytical mind-set, such 21st century historical phenomena.